ANALISIS PROSES PENAGIHAN PIUTANG PELANGGAN DI PT TANGKAS CIPTA OPTIMAL, JAKARTA - Widowati, Retno; Estiana, Ria; Syaputra, Yudhi Widian (JAB (Jurnal Akuntansi & Bisnis), 2021)
This research was conducted to find out how the process of collecting customer receivables at PT. Tangkas Cipta Optimal, Jakarta, to find out the constraints and alternative solutions in problem solving. Data collection techniques through observation and interviews, namely observing directly the object under study and with documentation. Based on the results of the discussion shows that the customer receivable collection process at PT. Tangkas Cipta Optimal, Jakarta has been implemented properly and in accordance with the applicable SOP (Standard Operating Procedure). And in accordance with the receivable collection process that is generally applicable in other companies. The obstacles that occur are the company's system is not supportive, there is a miss communication between employees, credit terms are not paid attention to, and there is an invoice request before the transaction is complete. Solutions made by PT. Tangkas Cipta Optimal, Jakarta, among others, the company reviews the system that has been used so far, improves communication between divisions, draws up an agreement with the debtor or if possible makes rules for penalties related to late payments and loads and sends performance invoices first to customers.Â Keywords: Process, Receivable Collection, Customers